The China-Pakistan Axis : Asia's New Geopolitics - Small, Andrew (India Random House, 2015)
China and Pakistan have been each other's only 'all-weather friend' for decades, but the relationship remains little understood. Small recounts the history of the Sino-Pakistani axis, including details on its most sensitive aspects, such as China's dealings with the Taliban and its support for Pakistan's nuclear programme. Today this relationship plays a central role in Asia's geopolitics, with ramifications for Afghanistan, India, Asia as a whole, and the West. Finally, Small discusses the dilemma China faces in maintaining its current relationship with Pakistan.
Include Notes, Bibliography and index
Keywords: China -- Pakistan -- Diplomatic relations